log-Series and log-Functions as application of multidual analysis - Messelmi, Farid (KOMUNITAS Analisis Matematika INDONESIA, 2023)
The purpose of this paper is to contribute to the development of the new concept of log-series and log-functions as particular continuation of real power series and real functions in multidual algebra. We will focus for the case of elementary log-functions and we propose some applications to special functions.